A theoretical study of cyclopentene (c-C5H8) dehydrogenation to cyclopentadienyl anion (c-C5H5−) on Ni (111) - German, Estefania (2009)
The cyclopentene (c-C5H8) dehydrogenation to cyclopentadienyl anion (c-C5H5−) on Ni (1 1 1) is studied using density functional theory (DFT) calculations. The Ni (1 1 1) surface was modeled through a unit cell of 64-atoms, while the preferred site and adsorption geometry corresponding to reactants and products were taken from previous works. We analyzed two possible mechanisms of reaction: a simultaneous dehydrogenation reaction, removing three hydrogen atoms at the same time, and a sequential dehydrogenation reaction, removing one hydrogen at a time. The geometry for each intermediate was also optimized. Results show that the sequential mechanism is kinetically favored over the simultaneous one. A bonding mechanism dominated by electron donation from H 1s orbital of cyclic intermediaries and c-C5H5− into the metal orbitals is also found.